Risk of Parkinson's disease among patients with psoriasis: A systematic review and meta-analysis - Patompong Ungprasert (Indian Journal of Dermatology, 2016)
Background: Patients with psoriasis might be at a higher risk of developing Parkinson's disease (PD) as a result of the detrimental effect of chronic inflammation on the neuronal tissue. This meta-analysis aimed to investigate this risk by comprehensively reviewing all available data. Methods: We conducted a systematic review and meta-analysis of cohort and case–control studies that reported relative risk, hazard ratio, odds ratio, or standardized incidence ratio comparing the risk of PD in patients with psoriasis versus subjects without psoriasis. Pooled risk ratio and 95% confidence interval (CI) were calculated using random-effect, generic inverse variance methods of DerSimonian and Laird. Results: Three retrospective studies and one case–control study met our eligibility criteria and were included in this meta-analysis. The pooled risk ratio of PD in patients with psoriasis versus participants without psoriasis was 1.38 (95% CI, 1.15–1.66). The statistical heterogeneity was low with an I2of 35%. Conclusions: Our meta-analysis demonstrated a statistically significant increased risk of PD among patients with psoriasis.